The determinants of Foreign Direct Investment (FDI) in Malaysia / Nur Shahniza Sapuwan - Sapuwan, Nur Shahniza (Faculty of Business Management, 2014)
Foreign Direct Investment (FDI) is a cross-border corporate governance mechanism through which a company obtains productive assets in another country. FDI is different from other major forms of foreign investment in that it is motivated largely by the long-term profit prospects in production activities that investor directly control (Wong H. , 2003).This research is to study on the determinants of Foreign Direct Investment (FDI) and there relationship between the Foreign Direct Investment (FDI) and its factors of inflow FDI in Malaysia such as infrastructure, exchange rate and market size. This study focuses on the FDI in Malaysia. The study is concentrates on the quantitative analysis using the secondary data that collected from the previous research and other sources. The sample of data used is from 2003 to 2013 and the data collected is in yearly basis. The statistical method that had been used in this research is multiple linear regression model.